Co-prescription of aripiprazole on prolactin levels in long-term hospitalized chronic schizophrenic patients with co-morbid type 2 diabetes: A retrospective clinical study - Liu, Xuebing; Sun, Xianzhi; Li, Lu; Zeng, Kuan; Li, Yi; Gao, Yujun; Ma, Jun (Frontiers in Psychiatry, 2023)
Background: One of the most frequent side effects of atypical antipsychotics is hyperprolactinemia (HPRL), and metformin or aripiprazole co-prescription is regarded as an effective therapy option for reducing prolactin (PRL) levels. However, whether either of the two drugs can reduce PRL levels in patients with long-term hospitalized chronic schizophrenia with co-morbid type 2 diabetes (T2DM) has not been adequately reported. Methods: In this study, there were 204 chronic schizophrenia patients with co-T2DM who did not receive an aripiprazole prescription and 197 chronic schizophrenia patients with co-T2DM who did (the co-Ari group). The two groups' variations in each target parameter were compared, and the variables affecting PRL levels were examined. Results: Compared to the non-Ari group, fasting blood glucose (FBG), blood uric acid (UA), total cholesterol (TC), triglyceride (TG), and low-density lipoprotein cholesterol (LDL-C) levels were significantly higher in the co-Ari group, but there was no difference in PRL levels. Co-prescribing aripiprazole had no impact on PRL levels in all patients with co-T2DM, and aripiprazole dose had no impact on PRL levels in the clinical subgroup of the co-Ari group. Conclusion: Aripiprazole not only worsened the severity of index disturbances associated to metabolism in long-term hospitalized chronic schizophrenia patients with co-T2DM on metformin-based hypoglycemic medications but also failed to lower PRL levels. Aripiprazole should not be used to lower prolactin levels in patients with chronic schizophrenia with co-T2DM.